Association of Knee Pain Frequency and Severity with Quadriceps Strength but Not Rate of Decline Over Four Years - David A. Sherman; Tuhina Neogi; Samantha Hornsby; David Felson; Michaell Lavalley; Joshua J. Stefanik; for the OAI investigators (ACR Open Rheumatology)
Objective Quadriceps weakness increases the risk of knee osteoarthritis (OA) and functional decline. Understanding how quadriceps strength changes over time is crucial for managing knee OA. Knee pain and effusion may influence strength over time through inhibition of motor pathways, but this remains a critical knowledge gap. We aimed to determine quadriceps strength trajectories and the association of knee pain and effusion among individuals with or at risk of knee OA. Methods We used baseline, two‐year, and four‐year quadriceps strength data from the Osteoarthritis Initiative to identify quadriceps strength trajectory groups using discrete mixture model clustering. Pain and effusion were assessed at baseline. We determined the relation of pain and effusion to trajectory groups using multinomial logistic regression, adjusted for demographics and radiographic OA. Results From 2,527 participants, three strength trajectories were identified for both sexes (“weak,” “average,” and “strong”), all with a linear decline in strength over four years. In women, individuals with frequent knee pain had higher odds of being in the weakest trajectory group compared to the average (odds ratio [OR] 0.54 [95% confidence interval (CI) 0.43–0.68]) and strong trajectories (OR 0.46 [95% CI 0.32–0.65]). Worse pain severity increased the odds of weakest trajectory group compared to the average (OR 0.89 [95% CI 0.85–0.93]) and strong strength trajectories (OR 0.86 [95% CI 0.80–0.92]). Effusion showed no association. Similar effects were present in men. Conclusion Frequent knee pain and knee pain severity were associated with being in a lower quadriceps strength trajectory group, but the rate of strength decline over four years was similar across all groups, suggesting that pain may not influence the rate of decline.